An INGO–corporate partnership in post-war Sri Lanka's agricultural sector. Issue 7 (3rd October 2021) - Senevirathna, Priyan
ABSTRACT: This practice note examines an INGO–Private Sector partnership involving the promotion of commercial agriculture in post-war Northern Sri Lanka. Current thinking suggests that the processes involved in such partnerships can strengthen global supply chains and ensure the socio-economic empowerment of producers within marginalised communities. The empirical evidence presented here illustrates, however, the impact of asymmetrical power relations upon intended outcomes. It shows the need for development actors to play a critical advocacy role and strengthen their bargaining power in such partnerships.